Análise do modelo de assistência em saúde mental na gestão Erundina - 1989-1992 - Migliari, Fabricia De Freitas Faria [UNIFESP] (2019)
Brazilian Psychiatric Reform was characterized by mental health care services restructuration and working process with new ways of care, it occurred from a political process of social transformation based on great political and social mobilization during Brazilian re-democratization process in the Health Reform context. Innovative experiences in Brazil particularly involving the mental health care in São Paulo city which was highlighted due to the intense aim of social, political and technical movements and its innovative approach of service networks. This study aims to analyze the mental health care model implanted in the period between 1989-1992 in the São Paulo City, disclosed by its collaborators; the technical-welfare and theoretical-conceptual influences in the choice of the implemented Mental Health Care model; to verify the changes undertaken by this Mental Health Care model and to analyze the influence of this implanted model in the changing of the mental illness social paradigm through participants' perception. We used the oral history method to revisit past experiences from the managers’ narrative of the Mental Health Program of the São Paulo city. As a result, we introduce the social political engagement of health professionals in student movements and, later, in the social movements of Mental Health against the hospital-centered model. The São Paulo City model was built inside the Mental Health Nucleus of the Workers Party (PT), its creators were linked to the unions, popular movement and a political party, with influences on the Health Reform conceptual ground and from the epistemological data of the population. The network of Mental Health Care was established in a decentralized and hierarchical way, consisting of Basic Health Units (UBS), UNCOVITI, Day Hospital (HD), General Hospital (HG), Emergency Room (PS), Therapeutic Residential Service SRT) and Coexistence and Cooperative Center (CECCO). The Model had a great impact on the amount of implemented services, reduction of hospitals beds and the closing of psychiatric hospitals. The health care professionals’ training and qualification, developed by this management, was one of the factors responsible for the transformation of psychiatric care and for the breaking of the paradigm of madness in society. Despite all innovation of the São Paulo City model, its purposes were not considered by Health Mental Care National Policy. The incorporated and chosen model was in the CAPS (Center of Psychosocial Attention) type implement format, which maintained the excluding view of the person with mental disorder of health services in general and society. We conclude that the choice of the assistance model in Mental Health, both in São Paulo City and in Brazil, was caused through the political bias, in agreement with the directions of the political-ideological groups.